Efektivitas Limbah Kulit Bawang Putih Sebagai Pigmen Organik Dalam Pembuatan Tinta Spidol (UNISTEK, 2022)
Garlic peel waste has the potential to be developed into products that have high economic value, one of which is as an alternative pigment raw material for the manufacture of marker ink. The manufacture of pigment ink itself can be done by adding gum arabic as a binder, 96% ethanol as a solvent, and polyethylene glycol (PEG) as an adhesion controller. This study aims to determine whether the skin of garlic (Allium Sativum L) can be used as the main raw material for environmentally friendly marker ink pigments. The study was conducted with variations in the concentration of gum arabic 1 gram, 1.5 grams, 2 grams, 2.5 grams, 3 grams, 3.5 grams with variations in stirring time of 10 minutes, 20 minutes and 30 minutes. The results of the ink that are close to commercial ink are ink with a variation of gum arabic as much as 1 gram with a stirring time of 10 minutes with a density of 1.114 gr/cm3, viscosity of 1.26 Poise, and transmission intensity 0 lux. Where the commercial ink standard which is calculated as a comparison has a density of 1.026 gr/cm3, a viscosity of 1.1 Poise, and a transmission intensity of 0 lux . Keywords : Garlic Peel, Marker Ink, Organic Pigment.